Comparison of Inflammation, Pain, and Recovery in Colorectal Cancer Patients Undergoing Surgery with General Anesthesia and Combined Epidural - Kenzi, Ignatio Armando; Hartawan, IGAG Utara; Sidemen, IGP Sukrana; Agung Senapathi, Tjokorda Gde; Gede Widnyana, I Made (Journal La Medihealtico, 2025)
Colorectal cancer has a high incidence and mortality rate. Surgery can increase the cytokine IL-6 which triggers inflammation and metastasis. The combination of general and epidural anesthesia has the potential to suppress IL-6, improve the tumor microenvironment, provide analgesia and improve postoperative recovery. To compare the effectiveness of postoperative analgesia quality in colorectal cancer patients receiving general anesthesia with combined epidural anesthesia. The single blind RCT study involved 44 patients who underwent surgery on colorectal cancer at Prof. Ngoerah Hospital. The study subjects were divided into two groups, group K who received general anesthesia and group P who received general anesthesia combined with epidural anesthesia. Patients' IL-6 will be evaluated preoperatively and 6 hours postoperatively. VAS and QOR-15 will be assessed 24 hours postoperatively. Of the 44 patients analyzed, the combined general anesthesia with epidural anesthesia group showed a significantly lower difference in IL-6 levels compared to the general anesthesia alone group of -14.69 [95% CI, p = <0.001]. The 24-hour postoperative VAS score was significantly lower than conventional general anesthesia, both in stationary and mobile conditions. In postoperative recovery, it was found that conventional general anesthesia combined with epdiural anesthesia gave greater QOR-15 results compared to conventional general anesthesia. General anesthesia combined with epidural anesthesia in colorectal cancer patients undergoing surgery can provide a lower difference in IL-6, lower VAS and higher QOR-15 postoperative satisfaction than the general anesthesia group.